Pharmacological and Structure-Activity Relationship Evaluation of 4-aryl-1-Diphenylacetyl(thio)semicarbazides - Wujec, Monika; Kędzierska, Ewa; Kuśmierz, Edyta; Plech, Tomasz; Wróbel, Andrzej; Paneth, Agata; Orzelska, Jolanta; Fidecka, Sylwia; Paneth, Piotr (My University, 2014)
This article describes the synthesis of six 4-aryl-(thio)semicarbazides (series a and b) linked with diphenylacetyl moiety along with their pharmacological evaluation on the central nervous system in mice and computational studies, including conformational analysis and electrostatic properties. All thiosemicarbazides (series b) were found to exhibit strong antinociceptive activity in the behavioural model. Among them, compound 1-diphenylacetyl-4-(4-methylphenyl)thiosemicarbazide 1b was found to be the most potentan algesic agent, whose activity is connected with the opioid system. For compounds from series a significant anti-serotonergic effect, especially for compound 1-diphenylacetyl-4- (4-methoxyphenyl)semicarbazide 2b was observed. The computational studies strongly support the obtained results.
Keywords: (thio)semicarbazides; conformational analysis; electrostatic properties; CNS activity; analgesic activity; serotonergic activity